2016
DOI: 10.18203/issn.2454-2156.intjscirep20162809
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization pattern during pregnancy in Nekemte referral hospital: a cross sectional study

Abstract: <p class="abstract"><strong>Background:</strong> Pregnancy is a period of great physiological changes to the mother and fetus in which every malfunction of the body as the result of drug use may lead to serious consequences in both. It is a period that demands special care to the health care service providers. Therefore, the objective of this project is to conduct across sectional study on drug utilization pattern during pregnancy in Nekemte referral hospital, Ethiopia from 2012-2013 that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(17 reference statements)
4
5
0
Order By: Relevance
“…The prevalence of drug utilization in this study was found to be 88.97%, comparable with prevalence of 85.1% in eastern Ethiopia, Harar [11], 87.5% in northern Ethiopia [9] and 88.4% in north west Ethiopia, Bahirdar [12]. But this value is lower than a study in Nekemte (96%) [13].…”
Section: Discussionsupporting
confidence: 69%
“…The prevalence of drug utilization in this study was found to be 88.97%, comparable with prevalence of 85.1% in eastern Ethiopia, Harar [11], 87.5% in northern Ethiopia [9] and 88.4% in north west Ethiopia, Bahirdar [12]. But this value is lower than a study in Nekemte (96%) [13].…”
Section: Discussionsupporting
confidence: 69%
“…This value was comparable with the study conducted in northern Ethiopia [8] and Bahirdar city [12] where the prevalence of drug use during pregnancy was found to be 87.5% and 88.4%, respectively. With reference to this finding, lower and higher drug utilization were also reported in studies conducted at Ayder referral hospital, Mekele (62.2%) [16] and Nekemte town (96%) [17], respectively. Almost half of the drug used in the current finding was during the first trimester of pregnancy where the critical period of organogenesis lies and drug-induced teratogenicity is assumed to reach climax.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, the overall prevalence of consumption of medications among pregnant women was 87.7%. This finding is comparable to the 87.5% in Northern Ethiopia [19] 88.4% in Bahr Dar city [28], 85.1% in Harer [15], 85.2% in Germany [20], but lower than the 96% in Nekemte City [32], 93-99% in France [20] and 93% in Iceland [33]. Moreover, the prevalence was higher than 71.3% in Addis Ababa [29], 73.2% in Cameroon [34], 79.1% in Netherlands [23], 65% in United Kingdom [24], and 56% in Canada [20].…”
Section: Discussionsupporting
confidence: 57%